2008
DOI: 10.1590/s0034-72992008000200012
|View full text |Cite
|
Sign up to set email alerts
|

Reabilitação fonatória do laringectomizado total: utilização de toxina botulínica na voz tráqueo-esofágica com prótese fonatória

Abstract: In tracheo esophageal puncture (TEP), we carry out a myotomy of the pharynx constrictor muscle; however, about 9 to 79% of patients need such procedure. The consequence of such procedure is an increase in salivary fistula rates in the postoperative. Botulin toxin is used in an outpatient basis. Aim: analyzing the efficacy of botulin toxin (BT) use in the rehabilitation of totally laryngectomized patients with tracheoesophageal voice (TEV) with spasms (S) of the pharyngoesophageal segment (PES) without myotomy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
(72 reference statements)
0
2
0
Order By: Relevance
“…Regarding myotomy, some authors have observed that there is a decrease in the peak of pharyngeal pressure and a decrease in spasms and hypertonicity in total laryngectomy patients (16,17,18,19) . In our study, none of the patients underwent these procedures.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding myotomy, some authors have observed that there is a decrease in the peak of pharyngeal pressure and a decrease in spasms and hypertonicity in total laryngectomy patients (16,17,18,19) . In our study, none of the patients underwent these procedures.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] have been done with the aim to investigate the efficiency of different surgical methods with a view to the most satisfactory possible prognostic in these patients affected by cancer.…”
Section: Methodsmentioning
confidence: 99%